1997
DOI: 10.1046/j.1525-1438.1997.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of endometrial stromalsarcoma in young women

Abstract: Lissoni A, Cormio G, Perego P, Gabriele A, Cantú MG, Bratina G. Conservative management of endometrial stromal sarcoma in young women. Int J Gynecol Cancer 1997; 7: 364-367. Endometrial stromal sarcoma (ESS) is a rare malignancy with an associated poor prognosis. Total abdominal hysterectomy is considered the treatment of choice, and the role of conservative, fertility-sparing surgery in young patients desiring pregnancy is not well-defined. Six patients were managed conservatively for ESS between 1982 and 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 14 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…Lei Yan et al reported a case of successful pregnancy after conservative treatment of ESS in a 25-year-old woman. TAH is the treatment of choice in these patients, but conservative management may be attempted in selected patients desiring pregnancy [3]. Considering the indolent growth of low grade ESS, definitive surgery can be postponed until after completion of reproductive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lei Yan et al reported a case of successful pregnancy after conservative treatment of ESS in a 25-year-old woman. TAH is the treatment of choice in these patients, but conservative management may be attempted in selected patients desiring pregnancy [3]. Considering the indolent growth of low grade ESS, definitive surgery can be postponed until after completion of reproductive function.…”
Section: Discussionmentioning
confidence: 99%
“…ESS can be mistaken for leiomyoma because clinical presentation mimics each other and often needs HPE to establish correct diagnosis [2,3]. In this article, we report a case of ESS in a young unmarried female of 23 years, which was misdiagnosed as leiomyoma, but the patient was able to conceive and deliver a healthy baby after debulking surgery to remove myoma was mistakenly done.…”
Section: Introductionmentioning
confidence: 93%
“…However, fertility‐sparing management is sometimes attempted for nulliparous young women, although the success of conservative management is unclear. Several ‘successful’ cases of the uterus being preserved after diagnosis of ESS have been reported after a short follow‐up period . Here, we report a fatal case after long‐term follow‐up.…”
Section: Introductionmentioning
confidence: 84%
“…Several 'successful' cases of the uterus being preserved after diagnosis of ESS have been reported after a short follow-up period. [2][3][4][5][6][7][8] Here, we report a fatal case after long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Careful monitoring with sonography followed by a ‘second‐look’ hysteroscopy and curettage is recommended. Pregnancy should then be allowed as soon as possible even through assisted reproductive therapy (76).…”
Section: Endometrial Cancermentioning
confidence: 99%